2009
DOI: 10.1177/070674370905401005
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity and Hopelessness as Predictors of Suicide-Related Ideation among Older Adults

Abstract: Objective: Research has demonstrated that impulsivity is strongly associated with suicide-related ideation and behaviour among young adults. However, to date, the potential importance of impulsivity as a predictor of suicide-related ideation in later life has yet to be determined. Our study examined impulsivity, hopelessness, depressive symptomatology, and sociodemographic factors vis-à-vis suicide-related ideation among older adults at risk of self-harm. Method:A sample (n = 117) of older adults was recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(45 citation statements)
references
References 25 publications
1
44
0
Order By: Relevance
“…It is also reported that older age, female sex, lower education levels, lower income levels, living with fewer household members, lower overall health status, poorer quality of life, and worsened health changes over the last year were significantly correlated with suicidal ideation [28]. Additional analysis indicated that the level of perceived filial piety receipt from older adults' perceptive was associated with increased risk of suicidal ideation [29]. More research is needed to examine the temporal relationship between filial piety and suicidal ideation.…”
Section: Discussionmentioning
confidence: 97%
“…It is also reported that older age, female sex, lower education levels, lower income levels, living with fewer household members, lower overall health status, poorer quality of life, and worsened health changes over the last year were significantly correlated with suicidal ideation [28]. Additional analysis indicated that the level of perceived filial piety receipt from older adults' perceptive was associated with increased risk of suicidal ideation [29]. More research is needed to examine the temporal relationship between filial piety and suicidal ideation.…”
Section: Discussionmentioning
confidence: 97%
“…This greater incidence of depression among the elderly may have affected the results of the present study 41,42) . Studies have recently reported changing patterns of impulsivity in different age groups and impulsivity is a risk factor for suicide attempts by the elderly 43,44) . A domestic study also reported that a high proportion of suicide attempts made by elderly patients via drug overdose were impulsive 45) .…”
Section: Discussionmentioning
confidence: 99%
“…The GSIS has demonstrated strong internal consistency among older adults (α = 0.91; Heisel and Flett 2006;Marty et al 2010) and significant 1-2 month test-retest reliability among nursing home residents (r = 0.86, p < 0.001; Heisel and Flett 2006). It has demonstrated criterion validity, differentiating mental health patients from nonpatients, construct validity with suicide ideation, hopelessness, depression, insomnia, impulsivity, poor coping strategies, and physical health complaints, and nonconvergence with MIL, PIL, psychological well-being, reasons for living, and subjective well-being (Heisel and Flett 2006Jahn et al 2011;Marty et al 2010;Nadorff et al 2013;Neufeld and O'Rourke 2009;Segal et al 2012). The GSIS has also shown sensitivity to clinical change in a small trial of Interpersonal Psychotherapy (IPT) adapted for older adults at-risk for suicide; study participants endorsed significantly less suicide ideation at posttreatment than at pretreatment assessment ).…”
Section: Methodsmentioning
confidence: 91%
“…Associations with hopelessness, depression, and late-life suicide ideation attest to the scale's validity (Heisel et al 2002(Heisel et al , 2005. The SHQ was included in this study given findings of a salient interpersonal element to hopelessness and suicide ideation and behavior among older adults (Duberstein et al 2004a, b;Heisel and Flett et al 2005;Howat and Davidson 2002;Neufeld and O'Rourke 2009). SHQ totals potentially ranged from 20-100.…”
Section: Methodsmentioning
confidence: 98%